An updated checklist of the orchids of Maharashtra, India - Singh Jalal, Jeewan (2018)
A checklist of the Orchidaceae of Maharashtra is presented based on herbarium collections and recent botanical explorations. This list comprises 32 genera with 106 taxa.The best represented genus is Habenaria, with 23 species, followed by Dendrobium with eleven, Eulophia and Oberonia with seven and Peristylus with six. In Maharashtra, the total endemic orchid species are 41 spread over in 13 genera. Of these 30, 6 species are endemic to Peninsular India and 5 species is endemic to India. Generally orchids are found in the nine major habitats in Maharashtra of which the best representation was observed in the semi-evergreen forests (55 species) followed by moist deciduous forests (48 species), high altitude rocky plateaus (26 species) and dry deciduous forests (25 species). In the checklist, flowering, habit, habitat, endemic status, distribution in Maharashtra are presented.